Reduced Fat Oxidation During Exercise in Post-Menopausal Overweight-Obese Women with Higher Lipid Accumulation Product Index - Stein, Elana; Silva, Igor Martins; Dorneles, Gilson P.; Lira, Fabio Santos [UNESP]; Romão, Pedro; Peres, Alessandra (Thieme, 2020)
BACKGROUND AND AIMS: The main aim of this study was to analyze how the lipid accumulation affects the whole-body fat oxidation over a range of intensities during a submaximal incremental exercise test in post-menopausal overweight-obese women. PATIENTS AND METHODS: The maximal fat oxidation (MFO), the intensity where the MFO occurs (FatMax), fat oxidation were measured over a range of intensities during a submaximal incremental exercise test through indirect calorimetry in 60 postmenopausal overweight-obese women (aged>49 years; body mass index 28.0 to 39.0 kg/m²). The metabolic profile of participants was evaluated and the LAP index was calculated (waist-58×triglycerides [mmol/L]). A cutoff point of 34.5 was adopted and participant were designed as low LAP index (n=30) or high LAP index (n=30). RESULTS: During submaximal exercise postmenopausal overweight-obese women with low LAP index showed a higher fat oxidation at 50% (0.53±0.05 vs. 0.45±0.12 g/min; p=0.01), 60% (0.40±0.06 vs. 0.31±0.16 g/min; p=0.02) and 70% (0.34±0.08 vs. 0.25±0.15 g/min; p=0.03) of VO2Peak than those with high LAP index. No significant difference was observed in carbohydrate oxidation between groups (p>0.05) during exercise. Moreover, a significant difference in absolute MFO (p=0.018), MFO relative to free fat mass (p=0.043) and FatMax (p=0.002) was identified. CONCLUSION: Postmenopausal overweight-obese women who showed unhealthy metabolic phenotype evaluated through LAP index presented low fat oxidation during a submaximal incremental exercise.